Letter - Cardiff Trades and Labour Council, 7 May 1926 (Cardiff)
1926-05-07 "Letter - Cardiff Trades and Labour Council, 7 May 1926" [g0143001.jpg], 7 May 1926, Cardiff Trades and Labour Council Local Organisation